Scripture and homosexuality : biblical authority and church today - Soards, Marion L. (Louisville, Kentucky : Westminster John Knox Press, 1995)
Focused and accessible, this book is an ideal starting point for the discussion of how the church should respond to and deal with issues of homosexuality.
Biblical authority and the reformed tradition-- The biblical understanding of homosexuality-- Thinking about the gospel and homosexuality-- Conclusions
Keywords: Homosexuality -- Biblical teaching; Homosexuality -- Religious aspects -- Christianity